2021
DOI: 10.25165/j.ijabe.20211405.4357
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of interaction effect between static and rolling friction of corn kernels on repose formation by DEM

Abstract: The coefficient of static friction (SF), the coefficient of rolling friction (RF) for particles are two key parameters affecting the repose angle formation and flow characteristics. In this paper, the interaction effects of SF and RF on the formation process of corn repose angle was investigated by the discrete element method. Firstly, five shape kinds of corn models (horse tooth, spherical cone, spheroid, oblate, and irregular shape) were established. Secondly, aluminum cylinder and organic glass box were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The contact force between particles was strongly correlated with the frictional characteristics of the surface of the particles [14]. Shi et al [15] explored the effects of particle sliding friction and rolling friction on the accumulation process. In addition, Cao et al [16] showed that the tangential force was higher when the bottom surface roughness was larger, and the corresponding "central depression" of the normal force was more obvious.…”
Section: Introductionmentioning
confidence: 99%
“…The contact force between particles was strongly correlated with the frictional characteristics of the surface of the particles [14]. Shi et al [15] explored the effects of particle sliding friction and rolling friction on the accumulation process. In addition, Cao et al [16] showed that the tangential force was higher when the bottom surface roughness was larger, and the corresponding "central depression" of the normal force was more obvious.…”
Section: Introductionmentioning
confidence: 99%
“…The contact parameters include the recovery coefficient, static friction, and rolling friction. The coefficient of static friction is 0.2 [25] , and the recovery coefficient is 0.182 [12] .…”
Section: Simulation Parametersmentioning
confidence: 99%
“…Differences in gravity center and irregular shape of maize seed can affect the flow properties. However, it was reduced by adjusting the coefficient of rolling friction of maize models [13,14,25,26] .…”
Section: Simulation Parametersmentioning
confidence: 99%
“…Because contact parameters such as the static friction coefficient and rolling friction coefficient significantly affect the repose angle [29], to obtain accurate friction coefficients, this paper subsequently uses the measured values of physical tests as the basis to select the range of values of the simulation test parameters. The repose angle is used to simulate and calibrate the friction coefficient.…”
Section: Rolling Friction Coefficientmentioning
confidence: 99%